2012
DOI: 10.9738/cc139.1
|View full text |Cite
|
Sign up to set email alerts
|

Mucocele of the Appendix: Case Report and Review of Literature

Abstract: Appendiceal mucocele is a rare disease. Sometimes it is discovered accidentally and sometimes it resembles acute appendicitis. Correct diagnosis before surgery is very important for the selection of adequate surgical treatment to avoid intraoperative and postoperative complications. Ultrasonography, and particularly computed tomography, should be used extensively for this purpose. If mucocele is treated incorrectly pseudomyxoma peritonei, which is characterized by malignant process, may develop. We present a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
67
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 25 publications
(42 reference statements)
0
67
0
2
Order By: Relevance
“…Finally, ischemia develops in the appendiceal wall, which weakens the epithelial integrity and increases the organ's risk of bacterial invasion. Although lymphoid hyperplasia and fecaliths are the most common causative factors of luminal obstruction, other less frequent factors have been associated with the condition, including enterobiasis, 1 endometriosis, 1,16,21 tuberculosis, 1 amebiasis, 1 actinomycosis, 1 adenovirus, 4 granulomatous diseases, 1,7,15,19 eosinophilic granuloma, 8 neurogenic appendicopathy, 11,12 foreign body melanosis, 4 neurofibroma, 4 diverticulitis, 1,9,20 and taeniasis, 1,17,21 as well as appendiceal malignancies, such as carcinoid tumor, 1,13,14 gastrointestinal stromal tumor, 1 hyperplastic polyp, 1 tubular adenoma, 1 villous adenoma, 1 mucocele, 10 mucinous cystadenoma, 1 adenocarcinoma, 1 mucinous cystadenocarcinoma, 1 lymphoma, 1 and leukemia. 1 This study was designed to investigate the occurrence and distribution of unusual pathologic findings encountered in appendectomy specimens of patients who had undergone surgery to treat an initial diagnosis of acute appendicitis.…”
mentioning
confidence: 99%
“…Finally, ischemia develops in the appendiceal wall, which weakens the epithelial integrity and increases the organ's risk of bacterial invasion. Although lymphoid hyperplasia and fecaliths are the most common causative factors of luminal obstruction, other less frequent factors have been associated with the condition, including enterobiasis, 1 endometriosis, 1,16,21 tuberculosis, 1 amebiasis, 1 actinomycosis, 1 adenovirus, 4 granulomatous diseases, 1,7,15,19 eosinophilic granuloma, 8 neurogenic appendicopathy, 11,12 foreign body melanosis, 4 neurofibroma, 4 diverticulitis, 1,9,20 and taeniasis, 1,17,21 as well as appendiceal malignancies, such as carcinoid tumor, 1,13,14 gastrointestinal stromal tumor, 1 hyperplastic polyp, 1 tubular adenoma, 1 villous adenoma, 1 mucocele, 10 mucinous cystadenoma, 1 adenocarcinoma, 1 mucinous cystadenocarcinoma, 1 lymphoma, 1 and leukemia. 1 This study was designed to investigate the occurrence and distribution of unusual pathologic findings encountered in appendectomy specimens of patients who had undergone surgery to treat an initial diagnosis of acute appendicitis.…”
mentioning
confidence: 99%
“…Among these four types, mucinous cystadenocarcinoma has the least developed etiology, and the clinical progression of the disease has not yet been determined. The clinical symptoms for mucinous cystadenocarcinoma may include right lower abdominal pain, palpable abdominal masses, weight loss, nausea, vomiting, gastrointestinal bleeding and signs of intestinal intussusception (13); however, in the present case, the disease presented as an umbilical hernia. In the present study, ultrasonography did not provide useful information, while the CT scan indicated peritoneal pseudomyxoma.…”
Section: Discussionmentioning
confidence: 48%
“…Although mucocele of the appendix is usually asymptomatic, symptomatically, it is most frequently observed as pain in the right lower quadrant. Apart from this, signs and symptoms such as palpable abdominal mass, nausea-vomiting, weight loss, and gastrointestinal bleeding can be encountered (9). In our case, there was no evidence of widespread abdominal pain and loss of appetite.…”
Section: Discussionmentioning
confidence: 72%